Providing a loan payment model to depositors of the banking system - Kiyani Ghaleh no, Rouhollah; Davrpanah, Ali Akbar (International Journal of Business Management and Entrepreneurship, 2022)
Purpose: One of the needs of customers in financial and credit institutions is the use of bank loans, and banks have a score calculation table for loan payments according to customers’ deposits. The main goal of this research is to provide a practical and optimal model for calculating facility scores. Methods: attracting deposits and paying bank loans in financial and credit institutions are different according to their statutes, the priority of some of them is to earn profit and the priority of specialized banks is to attract resources to pay loans in their specialized field of activity. By obtaining the required parameters, this research calculates the loan score for depositors in line with the variety of policies. At the same time, the basis of the work is based on mathematical calculations. Findings: Providing a mathematical model for decision makers in the financial field, with the ability to support a variety of strategies, is the main finding of this research. Conclusion: First, a basic formula for balancing loans with deposits has been presented. In the second step, the formula has been developed in such a way that the balance is established after deducting a coefficient from the deposit, and finally, the calculation formula has been developed for the addition of bank interest to the financial process. At the end of the article, the formulas are confirmed.